Master your motivation - Meurisse,Thibaut (2019)
"Master Your Motivation" is about understanding and harnessing your inner drive to achieve personal and professional goals. Motivation can fluctuate, but mastering it means learning how to maintain and channel it effectively. This involves setting clear and achievable goals, building positive habits, and visualizing success. Overcoming obstacles and maintaining resilience through challenges is crucial, as is celebrating small victories to keep morale high. Additionally, seeking support and accountability from others can further boost motivation. Ultimately, mastering motivation is a continuous process of self-awareness, discipline, and focused action.
"Master Your Motivation" is a concept that emphasizes taking control of your inner drive and harnessing it effectively to achieve personal and professional goals. Motivation is the psychological force that initiates, guides, and sustains goal-oriented behavior. However, it can fluctuate due to various factors like environment, mindset, and life circumstances. Mastering motivation means learning how to maintain, renew, and channel this energy to work in your favor, especially when challenges arise. To master motivation, one must first understand its different types. There are intrinsic motivations (driven by internal factors such as personal satisfaction and growth) and extrinsic motivations (driven by external rewards like money, recognition, or success). Mastery involves identifying what truly drives you and finding a balance between these types to maintain long-term commitment and enthusiasm.
Keywords: Positive Habits; Visualization Techniques